Applying the Morlet wavelet in a study of variability of the level of Paraguay river at Ladário, MS - Sá, Leonardo Deane de Abreu; Sambatti, Sabrina Bérgoch Monteiro; Galvão, Geraldo Pereira (Pesquisa Agropecuaria Brasileira, 1998)
The Morlet complex wavelet was used to study the scales when the level of Paraguay River in Ladário (MS) is more variable. A series of daily data of the river, from January 1900 to June 1995, was used. The following relevant results were obtained: (a) important dominant variability was noticed at the annual scale, that was stationary; (b) important variability in the interval of scales from 2 to 5 years, was detected, which was not stationary; (c) another striking variability in the interval of scales from 10 to 11 years, approximately, which was not plainly stationary, was observed; (d) regions were found with lines of phase convergence in the time-scale signal phase analysis diagram. These conclusions are discussed and compared to other investigations on the variability of hydrometeorologic data.
Keywords: hidrometeorology; Paraguay river; variability; wavelet; singularities; Pantanal wetland